2021
DOI: 10.1038/s41467-021-23987-z
|View full text |Cite
|
Sign up to set email alerts
|

FoxG1 regulates the formation of cortical GABAergic circuit during an early postnatal critical period resulting in autism spectrum disorder-like phenotypes

Abstract: Abnormalities in GABAergic inhibitory circuits have been implicated in the aetiology of autism spectrum disorder (ASD). ASD is caused by genetic and environmental factors. Several genes have been associated with syndromic forms of ASD, including FOXG1. However, when and how dysregulation of FOXG1 can result in defects in inhibitory circuit development and ASD-like social impairments is unclear. Here, we show that increased or decreased FoxG1 expression in both excitatory and inhibitory neurons results in ASD-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 82 publications
(115 reference statements)
4
45
0
Order By: Relevance
“…Consistent with published work(14), we found decreased interest to a novel mouse in the 3-Chamber test, however in contrast we found increased rather than decreased sociability in the same task (Table 3). These experiments were conducted at different ages and future longitudinal studies will be needed to determine if this social interaction difference is age related or a function of different Foxg1 alleles or background strains.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with published work(14), we found decreased interest to a novel mouse in the 3-Chamber test, however in contrast we found increased rather than decreased sociability in the same task (Table 3). These experiments were conducted at different ages and future longitudinal studies will be needed to determine if this social interaction difference is age related or a function of different Foxg1 alleles or background strains.…”
Section: Discussionsupporting
confidence: 93%
“…While both studies were conducted at roughly the same age, the caveats regarding specific allele and strain mentioned above remain. A recent study identified deficits in working memory using the 8-arm radial maze in a different allele of Foxg1 (14). Together these results across different Consistent with published work (14), we found decreased interest to a novel mouse in the 3-Chamber test, however in contrast we found increased rather than decreased sociability in the same task (Table 3).…”
Section: Heterozygous Foxg1 Mice Have Alterations In Social Behaviorsupporting
confidence: 91%
See 2 more Smart Citations
“…Loss of Foxg1 leads to defective social interaction and impaired spatial learning and memory [12,16]. A concomitant misregulation of Foxg1 in postnatal, gabaergic and glutamatergic neurons, is necessary and sufficient to trigger autism spectrum disorder-like (ASD-like) phenotypes [17].…”
Section: Introductionmentioning
confidence: 99%